Kajian Tanda dan Makna Kampanye Pilkada DKI Jakarta 2017 di Media Sosial Instagram - Andika Indrayana; Raissa Salsabil (DeKaVe, 2018)
Abstract.This research aims to reveal the meaning of campaign activity on Instagram by three candidates of Jakarta’s regional leader election in 2017: Agus Harimurti Yudhyono-Sylviana Murni as candidate number one,  Basuki Tjahaja Purnama-Djarot Saiful Hidayat as candidate number two, and Anies Baswedan-Sandiaga Uno as candidate number three. Using structural semiotics, this research show that: (1) every posts created by the candidates tend to have no correlation between verbal and visual sign. Every signs produces autonomy meaning, and; (2) by visual, every candidates’s posts style (verbal and visual), influenced by their prefesion.Keywords: Instagram, Political Campaign, Social Media, Structural Semiotics.